2016
DOI: 10.1021/acs.organomet.6b00265
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor-Controlled Chirality of Tropoisomeric Ligand

Abstract: A new tropos ligand with an integrated anion receptor site has been prepared. Chiral carboxylate and phosphate anions that bind in the anion receptor unit proved capable of stabilizing chiral conformations of the achiral flexible bidentate biaryl phosphite ligand, as shown by variable temperature 1 H and 31 P NMR spectroscopical studies of palladium(0) olefin complexes. Palladium allyl complexes of the supramolecular ligand-chiral cofactor assemblies catalyzed asymmetric allylic substitutions of rac-(E)-1,3-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…and Error! Reference source not found.. 35 The addition of an enantiopure acid derivative as the RA (or "cofactor" as referred to by the authors) broke the symmetry of the diamidodiindolylmethane fragment in ligand L14 and generated preferred conformations in the conformationally labile phosphite groups. NMR spectroscopy studies showed that hydrogen bonding between the NH groups in ligand L14 and the oxyanions was at the origin of the chirogenesis processes taking place.…”
Section: Supramolecular Regulation On a Pro-chiral Ligandmentioning
confidence: 99%
“…and Error! Reference source not found.. 35 The addition of an enantiopure acid derivative as the RA (or "cofactor" as referred to by the authors) broke the symmetry of the diamidodiindolylmethane fragment in ligand L14 and generated preferred conformations in the conformationally labile phosphite groups. NMR spectroscopy studies showed that hydrogen bonding between the NH groups in ligand L14 and the oxyanions was at the origin of the chirogenesis processes taking place.…”
Section: Supramolecular Regulation On a Pro-chiral Ligandmentioning
confidence: 99%
“…Rhodium and platinum complexes were analyzed through ac ombination of NMR studies,E SI-MS measurements,a sw ell as UV-VIS and circular dichroism spectroscopy. This transfer has been achieved by coordination of achiral co-ligand or anion, [7][8][9][10][11] or control of the backbone by acovalently bound chiral auxiliary (Scheme 1). [1][2][3][4] However, the asymmetric synthesis of such an inflexible (atropos) backbone is often long and difficult.…”
mentioning
confidence: 99%
“…This transfer has been achieved by coordination of achiral co-ligand or anion, [7][8][9][10][11] or control of the backbone by acovalently bound chiral auxiliary (Scheme 1). [9,28] Also chiral phosphoric acids have been used for supramolecular stereoregulation through ion pairing in asymmetric catalysis. [17,18] In this manner, ab y-design nonlinear amplification of stereoselectivity was achieved.…”
mentioning
confidence: 99%
See 2 more Smart Citations